PENGARUH HARGA, PROMOSI, KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN, DAN LOYALITAS KONSUMEN PADA PRODUK DISKON DI HYPERMART PONTIANAK - admin, Reci Andika B11111023 (Jurnal Manajemen Update, 2015)
This research is motivated by a survey conducted by AC Nielsen that in buying the product obtained by 76% of consumers like discounts, while 18% prefer a direct gift in 2015. The increase in purchase discount product label Hypermart indicates that a change in the behavior of consumer purchasing decisions Pontianak Society toward the discount product label Hypermart. By looking at existing problems, this research is directed to analyze on several factors such as; price, promotion, product quality that could be expected to influence consumer purchasing decisions and their impact on consumer loyalty in Hypermart Pontianak. The research data was collected from 100 respondents who bought the discount product label Hypermart. The analysis showed that price, promotion, product quality has a positive and significant influence on purchasing decisions while prices have no influence on customer loyalty. Keywords: price, promotion, product quality, purchasing decisions,                             consumer loyalty.